PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP HASIL BELAJAR SISTEM BAHAN BAKAR BENSIN - I Made Adwesta Wirya; Wiyogo; Jhonni Rentas Duling (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2019)
The purpose of this study was to determine the Effect of Contextual Teaching and Learning (CTL) Model on ??Student Learning Outcomes on Conventional Gasoline Fuel Systems Lesson in TBSM XI Class of SMKN 1 Palangka Raya, Academic Year 2017/2018. The method used in this study is pre-experimental design, by using one-group pretest-posttest design. In this design there is a pretest before treatment. Thus the results of the treatment can be known more accurately, because it can compare with the situation before being treated. The results of this study indicate that the calculation using the t-test with a significance level of ? = 0.05 obtained a t-count value of 16.19 while the t_table value was 1.992. Because t_count > t_table, this means that H0 is rejected and H1 is accepted, so it can be concluded that there are influences of student learning outcomes taught using the CTL model on conventional gasoline fuel system lesson. The type of learning model is quite effective in the process of teaching in schools especially automotive lesson.